2020
DOI: 10.1051/parasite/2020051
|View full text |Cite
|
Sign up to set email alerts
|

Bat parasites (Acari, Anoplura, Cestoda, Diptera, Hemiptera, Nematoda, Siphonaptera, Trematoda) in France (1762–2018): a literature review and contribution to a checklist

Abstract: This paper is a bibliographical survey of records of bat parasites in France (including Corsica) between 1762 and 2018. In total, 237 scientific publications were analysed. They show that bats are infected with a large diversity of endoparasites and ectoparasites. A total of 113 parasite taxa were identified from 27 host species; in addition, six bats were not identified to the species-level. The helminth fauna of bats comprises three species of Cestoda, 15 of Trematoda, and 13 of Nematoda. Acari parasites inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 95 publications
(334 reference statements)
0
2
0
Order By: Relevance
“…Their deutonymphs do not exhibit any adaptations to phoresis, nor have they ever been observed on insects or myriapods. They are also unlikely to be carried by bats, as research on the mites they carry has been fairly extensive, including research on the common noctule analysed in this study, as, so far, their presence has not been observed [44][45][46][47][48]. Consequently, deutonymphs are most likely carried by birds, especially since the specific structure of the barbs allows the deutonymphs to 'hook' onto feathers.…”
Section: Discussionmentioning
confidence: 99%
“…Their deutonymphs do not exhibit any adaptations to phoresis, nor have they ever been observed on insects or myriapods. They are also unlikely to be carried by bats, as research on the mites they carry has been fairly extensive, including research on the common noctule analysed in this study, as, so far, their presence has not been observed [44][45][46][47][48]. Consequently, deutonymphs are most likely carried by birds, especially since the specific structure of the barbs allows the deutonymphs to 'hook' onto feathers.…”
Section: Discussionmentioning
confidence: 99%
“…However, while hundreds of nematodes have been described in bats (2), their biology, life cycles and host-parasite specificity and interactions remain largely unknown (3). Onchocercid filarial nematodes, and especially the genera Litomosa and Litomosoides, occur relatively frequently in both Old World and Nearctic and Neotropical bats of the families Hipposideridae, Miniopteridae, Molossidae, Phyllostomidae, Pteropidae, Rhinolophidae and Vespertilionidae (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Adult Litomosa and Litomosoides generally reside within the pleural and/or peritoneal cavities of bats; however, cerebral ventricles (14) or the pulmonary artery, the right ventricle of the heart and the portal vein (9), may also be favoured sites for some adult onchocercid filariae.…”
Section: Introductionmentioning
confidence: 99%